Pronomes em parkatêjê: a expressão da terceira pessoa - SILVA, Nandra Ribeiro (Universidade Federal do Pará, 2017)
The Parkatêjê language is a member of the Timbira dialect complex spoken in the southeast of Pará, near the town of Bom Jesus do Tocantins. This language has two series of personal pronouns (free and bound) that receive case and number markers. The two series, according to Ferreira (2003), distinguish first and second persons, however a specific form for the third person referents had not been described. This dissertation describes the expression of the third person in Parkatêjê pronominals, and compares them to the third person pronouns forms described for other northern Jê languages, such as Mēbēngokrê, Krahô, Pykobjê and Apãniekrá.